Loop-gap microwave resonator for millimeter-scale diamond quantum sensor - Nishitani, Daisuke; Shibata, Takayuki; Oyama, Kazuhiro; Cheng, Fan; Hatano, Yuji; Teraji, Tokuyuki; Onoda, Shinobu; Ohshima, Takeshi; Iwasaki, Takayuki; Hatano, Mutsuko (Materials Today Communications, 2022)
The diamond quantum sensors based on NV (Nitrogen-Vacancy) center is one of the promising candidates for magnetoencephalography, which requires sub-pT/√Hz magnetic field sensitivity. To achieve high sensitivity, it is necessary to excite millimeter volume scale in diamond crystal by light and microwaves, and to collect fluorescence efficiently emitted from NV centers in the volume. We proposed and fabricated a printed circuit board-based loop-gap microwave resonator to improve the spatial uniformity of the microwave field to the millimeter volume scale. Moreover, our resonator can incorporate features such as efficient optical excitation and collection, and heat dissipation. Using this resonator, we demonstrated that the NV ensemble, formed by CVD process, were driven within an area of 5 mm square. The average strength of the microwave magnetic field was 0.53 G at 46 dBm input power, which is sufficient to drive the NV centers for our sensor. The uniformity of the microwave field strength was within 0.27G of the peak-to-peak amplitude for 1 mm3 volume. Differential input of microwaves into a loop-gap resonator with two gaps improves the peak-to-peak amplitude for 1 mm3 to 0.093 G in the simulation. [Display omitted] •Loop-gap resonator fabricated with multilayer printed circuit boards.•Resonator capable of driving a 1 mm3 NV center.•Resonator for optical excitation of diamond side surface.